2015
DOI: 10.1016/j.bone.2015.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Multiscale biomechanical responses of adapted bone–periodontal ligament–tooth fibrous joints

Abstract: Reduced functional loads cause adaptations in organs. In this study, temporal adaptations of bone-ligament-tooth fibrous joints to reduced functional loads were mapped using a holistic approach. Systematic studies were performed to evaluate organ-level and tissue-level adaptations in specimens harvested periodically from rats given powder food for 6 months (N = 60 over 8,12,16,20, and 24 weeks). Bone-periodontal ligament (PDL)-tooth fibrous joint adaptation was evaluated by comparing changes in joint stiffness… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 43 publications
1
20
0
Order By: Relevance
“…The teeth used for biomechanical testing were imaged [ 15 ] by microcomputed tomography (Viva CT 80, Scanco Medical), as shown in Fig. 1 .…”
Section: Methodsmentioning
confidence: 99%
“…The teeth used for biomechanical testing were imaged [ 15 ] by microcomputed tomography (Viva CT 80, Scanco Medical), as shown in Fig. 1 .…”
Section: Methodsmentioning
confidence: 99%
“…Another study suggested that the alveolar trabecular bone loss induced by occlusal hypofunction is correlated with a decrease in the number of osteoclasts, and this bone resorption causes a reduction in bone volume to the minimum necessary in the absence of forces stimulating the alveolar bone, such as occlusal force, in growing rats [39] . Also, a soft diet affected the turnover of periodontal ligament collagen and altered the bone dynamics of the tooth furcation area in young rats [40] . In a histological study, a 4-week powdered diet resulted in trabecular bone loss and enlargement of the bone marrow cavity; however, trabeculae attached to the periodontal ligament remained in the maxilla and mandible of the rats [30] .…”
Section: Impact Of Differences In Feeding Behavior On Jaw Bone Metabomentioning
confidence: 99%
“…In mammalian species, function-related thresholds are most often modulated by food hardness (7, 34, 9194). Previous studies have shown that the width of the PDL-space changes in response to magnitude and direction of occlusal loads (7).…”
Section: Bone-periodontal Ligament-tooth Fibrous Jointmentioning
confidence: 99%
“…Previous studies have shown that the width of the PDL-space changes in response to magnitude and direction of occlusal loads (7). Hyperfunction during which force exceeds physiologic loading (increased magnitude and decreased frequency) has shown to increase PDL-space through an upregulated osteoclastic response, while conditions of hypofunction (decreased magnitude and increased frequency) illustrated modeling of the PDL width to a narrower space than under control conditions (17, 34, 78, 83, 95).…”
Section: Bone-periodontal Ligament-tooth Fibrous Jointmentioning
confidence: 99%